Pengaruh Self-Regulated Learning, Self-Efficacy dan Perhatian Orangtua Terhadap Prestasi Belajar Matematika Siswa - Sugiyana Sugiyana (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
The purpose of this study was to determine the effect of self regulated learning, self efficacy and parents Â attention to learning achievement in mathematics in class VIII. This study took place in SMPN 1 Gunung Purwosari. Number of samples 89 and take the entire eighth grade students as subjects. Methods of data collection using a scale of self regulated learning, self-efficacy scale, and scale attention parents. Mathematics learning achievement data obtained from the documents in the first semester report cards while collecting data in the second semester. Data analysis technique used is multiple regression analysis. 0,05).">The regression analysis showed significant results between Self Regulated Learning on Mathematics Learning Achievement of 0.516 (516> 0.05). 0,05).">Self-efficacy on mathematics learning achievement of 0.611 (0.611> 0.05). 0,05), hal ini menunjukkan tidak ada pengaruh dari ketiga variabel tersebut terhadap prestasi belajar matematika.">Attention parents of the mathematics learning achievement of 0.193 (0.193> 0.05), it showed no effect of these three variables on mathematics achievement. Self regulated learning, self-efficacy and attention parents contributed 2.8% of the Mathematics Learning Achievement. 0,05), Self Regulated Learning, Self-efficacy, dan Perhatian Orangtua secara bersama-sama tidak berpengaruh terhadap Prestasi Belajar Matematika, berarti dipengaruhi oleh faktor lain yang tidak diteliti.">Significance analysis of variance of 0.494 (0.494> 0.05), self regulated learning, self-efficacy, and attention parents together does not affect the learning achievement of Mathematics, means influenced by other factors not examined. It is concluded that there is no significant effect either jointly or individually between self-regulated learning, self-efficacy and attention parents of the mathematics learning achievement. This research can be taken into consideration in making a program improvement school mathematics achievement.